Arrest chemokines - Klaus Ley (Frontiers Research Topics, 2015)
Arrest chemokines are a small group of chemokines that promote leukocyte arrest from rolling by triggering rapid integrin activation. Arrest chemokines have been described for neutrophils, monocytes, eosinophils, naïve lymphocytes and effector memory T cells. Most arrest chemokines are immobilized on the endothelial surface by binding to heparin sulfate proteoglycans. Whether soluble chemokines can promote integrin activation and arrest is controversial (Alon-Gerszten). Many aspects of the signaling pathway from the GPCR chemokine receptor to integrin activation are the subject of active investigation. Leukocyte adhesion deficiency III is a human disease in which chemokine-triggered integrin activation is defective because of a mutation in the cytoskeletal protein kindlin-3. About 10 different such mutations have been described. The defects seen in patients with LAD-III elucidate the importance of rapid integrin activation for host defense in humans. We welcome reports that help clarifying this crucial first step in the process of leukocyte transendothelial migration.